School Committee Empowerment through Management and Partnership Training in Supporting the Educational SDGs - Dias Andris Susanto; Ajeng Setyorini; Andi Priyolistiyanto; Moses Adeleke Adeoye (LPPM Universitas Timor, 2026)
School committees play a strategic role in community-based educational governance. However, many school committees still lack a comprehensive understanding of their roles, functions, and mechanisms for building partnerships with schools and the wider community. This community service program aimed to empower school committee members through training in institutional management and school-community partnership strategies. The activity was conducted at SD Negeri Jatingaleh 01 in Semarang City, representing the Candisari District area. The approach employed was Participatory Action Learning (PAL) and Capacity Building, comprising several stages: needs assessment, training, assistance in preparing annual work plans, and the formation of a school-community partnership forum. The results showed a significant improvement in the understanding and skills of school committee members, the successful development of annual work programs, and the implementation of collaborative school-community initiatives. This intervention aligns with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals). The program is recommended for replication in other school clusters with policy support from local governments)